2008
DOI: 10.1182/blood-2008-03-144899
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory polymorphism in vitamin K epoxide reductase complex subunit 1 (VKORC1) affects gene expression and warfarin dose requirement

Abstract: Warfarin dose requirements have been associated with 2 main haplotypes in VKORC1, but the responsible polymorphisms remain unknown. To search for regulatory polymorphisms, we measured allelic mRNA expression of VKORC1 in human liver, heart, and B lymphocytes. The observed 2-fold allelic mRNA expression imbalance narrowed possible candidate SNPs to ؊1639G>A and 1173C Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
147
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(161 citation statements)
references
References 46 publications
10
147
0
4
Order By: Relevance
“…The fact that in vitro transient transfection assays failed to recapitulate validated expression differences in the reporter gene system could either reflect that the true functional SNP was not included in our genotyped sites but is in strong LD with them or that the requirement of additional regulatory elements (i.e., proper sequence and chromatin context) or transcription factors were not present in the reporter gene system used. The latter possibility is highlighted by recent studies observing disconnection between in vitro transfection assay results and in vivo determined genetically controlled expression (Cirulli and Goldstein 2007;Wang et al 2008). …”
Section: Discussionmentioning
confidence: 96%
“…The fact that in vitro transient transfection assays failed to recapitulate validated expression differences in the reporter gene system could either reflect that the true functional SNP was not included in our genotyped sites but is in strong LD with them or that the requirement of additional regulatory elements (i.e., proper sequence and chromatin context) or transcription factors were not present in the reporter gene system used. The latter possibility is highlighted by recent studies observing disconnection between in vitro transfection assay results and in vivo determined genetically controlled expression (Cirulli and Goldstein 2007;Wang et al 2008). …”
Section: Discussionmentioning
confidence: 96%
“…34 This may result from decreased production of VKORC1 mRNA by the -1639A allele and reduced expression of the enzyme VKOR. 35 As a result of the reduced expression of VKOR, less warfarin is needed in patients carrying the -1639A promoter variant to maintain the target INR. Population studies have shown that the VKORCI -1639A allele predominates in people of Asian descent but is less common in white people and those of African descent.…”
Section: Incidence Of Warfarin-related Adesmentioning
confidence: 99%
“…Su polimorfismo -1639G>A (rs9923231) se asocia con la sensibilidad a la warfarina y la disminución de la cantidad requerida (2). Se ha observado una asociación preferencial con la cromatina activa del alelo G en la posición -1639 del VKORC1, mientras que el alelo menor A en esta misma posición genera un sitio de unión E-box de tipo supresor, lo que resulta en una menor síntesis de ARN (12).…”
unclassified